The Influence of Transformational Leadership and Organizational Culture on Organizational Citizenship Behavior Through Organizational Commitment as an Intervening Variable: Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi terhadap Organizational Citizenship Behavior Melalui Komitmen Organisasi sebagai Variabel Intervening - Fanani, Achmad Muhajir; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of Transformational Leadership and Organizational Culture on Organizational Citizenship Behavior through Organizational Commitment as an Intervening variable study PT. Moya Kasri Wira East Java. This research was conducted using quantitative methods with the sample used in this PT. Moya Kasri Wira East Java. This research used the program smartPLS 3.0.Based on the results of the analysis it can be concluded that Transformational Leadership has a significant effect on OCB, Organizational Culture has a significant effect on OCB, Transformational Leadership has a significant effect on Organizational Commitment, Organizational Culture has a significant effect on Organizational Commitment, Organizational Commitment has a significant effect on OCB, Transformayional Leadership has a significant effect on OCB trhough Oganizational Commitment, Organizational Culture has a significant effect on OCB trhough Organizational Commitment.